'HIV is like a tsotsi. ARVs are your guns': associations between HIV-disclosure and adherence to antiretroviral treatment among adolescents in South Africa. (June 2015) - Cluver, Lucie D.; Hodes, Rebecca J.; Toska, Elona; Kidia, Khameer K.; Orkin, F. Mark; Sherr, Lorraine; Meinck, Franziska
Abstract : Objectives: WHO guidelines recommend disclosure to HIV-positive children by school age in order to improve antiretroviral therapy (ART) adherence. However, quantitative evidence remains limited for adolescents. This study examines associations between adolescent knowledge of HIV-positive status and ART-adherence in South Africa. Design: A cross-sectional study of the largest known community-traced sample of HIV-positive adolescents. Six hundred and eighty-four ART-initiated adolescents aged 10–19 years (52% female, 79% perinatally infected) were interviewed. Methods: In a low-resource health district, all adolescents who had ever initiated ART in a stratified sample of 39 health facilities were identified and traced to 150 communities [ n = 1102, 351 excluded, 27 deceased, 40 (5.5%) refusals]. Quantitative interviews used standardized questionnaires and clinic records. Quantitative analyses used multivariate logistic regressions, and qualitative analyses used grounded theory for 18 months of interviews, focus groups and participant observations with 64 adolescents, caregivers and healthcare workers. Results: About 36% of adolescents reported past-week ART nonadherence, and 70% of adolescents knew their status. Adherence was associated with fewer opportunistic infection symptoms [odds ratio (OR) 0.55; 95% CI 0.40–0.76]. Adolescent knowledge of HIV-positive status was associated with higher adherence, independently of all cofactors (OR 2.18; 95% CI 1.47–3.24). Among perinatally infected adolescents who knew their status ( n = 362/540), disclosure prior to age 12 was associated with higher adherence (OR 2.65; 95% CI 1.34–5.22). Qualitative findings suggested that disclosure was undertaken sensitively in clinical and family settings, but that adults lacked awareness about adolescent understandings of HIV status. Conclusion: Early and full disclosure is strongly associated with improved adherence amongst ART-initiated adolescents. Disclosure may be an essential tool in improving adolescent adherence and reducing mortality and onwards transmission.